Identification of a new member of Mortaparib class of inhibitors that target mortalin and PARP1 - Meidinna, Hazna Noor; Shefrin, Seyad; Sari, Anissa Nofita; Zhang, Huayue; Dhanjal, Jaspreet Kaur; Kaul, Sunil C.; Sundar, Durai; Wadhwa, Renu (Frontiers in Cell and Developmental Biology, 2022)
Mortalin, a heat shock family protein enriched in cancer cells, is known to inactivate tumor suppressor protein p53. Abrogation of mortalin-p53 interaction and reactivation of p53 has been shown to trigger growth arrest/apoptosis in cancer cells and hence, suggested to be useful in cancer therapy. In this premise, we earlier screened a chemical library to identify potential disruptors of mortalin-p53 interaction, and reported two novel synthetic small molecules (5-[1-(4-methoxyphenyl) (1,2,3,4-tetraazol-5-yl)]-4-phenylpyrimidine-2-ylamine) and (4-[(1E)-2-(2-phenylindol-3-yl)-1-azavinyl]-1,2,4-triazole) called Mortaparib and MortaparibPlus, respectively. These compounds were shown to possess anticancer activity that was mediated through targeting mortalin and PARP1 proteins, essential for cancer cell survival and proliferation. Here, we report characterization of the third compound, 4-[(4-amino-5-thiophen-2-yl-1,2,4-triazol-3-yl)sulfanylmethyl]-N-(4-methoxyphenyl)-1,3-thiazol-2-amine, isolated in the same screening. Extensive computational and molecular analyses suggested that the new compound has the capability to interact with mortalin, p53, and PARP1. We provide evidence that this new compound, although required in high concentration as compared to the earlier two compounds (Mortaparib and MortaparibPlus) and hence called MortaparibMild, also downregulates mortalin and PARP1 expression and functions in multiple ways impeding cancer cell proliferation and migration characteristics. MortaparibMild is a novel candidate anticancer compound that warrants further experimental and clinical attention.